DETERMINATION OF THE PETROLOGIC TYPE OF CV3 CHONDRITES BY RAMAN SPECTROSCOPY OF INCLUDED ORGANIC MATTER - Bonal L.; Quirico E.; Bourot-Denise M.; Montagnac G. (My University, 2006)
This paper reports the first reliable quantitative determination of the thermal metamorphism grade of a series of nine CV3 chondrites: Allende, Axtell, Bali, Mokoia, Grosnaja, Efremovka, Vigarano, Leoville, and Kaba. The maturity of the organic matter in matrix, determined by Raman spectroscopy, has been used as a powerful metamorphic tracer, independent of the mineralogical context and extent of aqueous alteration. This tracer has been used along with other metamorphic tracers such as Fe zoning in type-I chondrules of olivine phenocrysts, presolar grain abundance and noble gas abundance (bulk and P3 component). The study shows that the petrologic types determined earlier by Induced ThermoLuminescence were underestimated and suggests the following values: PT (Allende-Axtell) >3.6; PT (Bali-Mokoia-Grosnaja) ?3.6; PT (Efremovka-Leoville-Vigarano) = 3.1-3.4; PT (Kaba) >3.1. The most commonly studied CV3, Allende, is also the most metamorphosed. Bali is a breccia containing clasts of different petrologic types. The attribution suggested by this study is that of clasts of the highest petrologic types, as pointed out by IOM maturity and noble gas bulk abundance. CV3 chondrites have complex asteroidal backgrounds, with various degrees of aqueous alteration and/or thermal metamorphism leading to complex mineralogical and petrologic patterns. (Fe,Mg) chemical zoning in olivine phenocrysts, on the borders of type I chondrules of porphyritic olivine- and pyroxene-rich textural types, has been found to correlate with the metamorphism grade. This suggests that chemical zoning in some chondrules, often interpreted as exchanges between chondrules and nebular gas, may well have an asteroidal origin. Furthermore, the compositional range of olivine matrix is controlled both by thermal metamorphism and aqueous alteration. This does not support evidence of a nebular origin and does not necessarily mirror the metamorphism grade through (Fe,Mg) equilibration. On the other hand, it may provide clues on the degree of aqueous alteration vs. thermal metamorphism and on the timing of both processes. In particular, Mokoia experienced significant aqueous alteration after the metamorphism peak, whereas Grosnaja, which has similar metamorphism grade, did not. ? 2005 Elsevier Inc. All rights reserved.
Keywords: CHONDRITE; METEORITE; ORGANIC MATTER